PENGARUH PROMOSI, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA TOKO BEAU MY BEAUTY SHOP DI DADAP SUKMAJAYA - Dinda Robian; Salman Paludi (LPPM Universitas Asa Indonesia, 2019)
This study aims to analyze how much influence the promotion, quality of service, and location to customer satisfaction in BEAU My Beauty Shop Dadap Sukmajaya. Population in this study people from customers BEAU My Beauty Shop Dadap Sukmajaya in May until July 2019 and Samples in this study100 respondents. Sampling method used is Purposive sampling Method. Analysis tools using multiple regression analysis. Based on the analysis, it can be concluded that, there is a real effect of promotion variables to the customer satisfaction with a contribution of 4,67%, There is a real influence of quality of service variable to customer satisfaction with contribution equal to 9,13%, There is a real influence of location variable to customer satisfaction with contribution equal to 20,17%. The independent variables, Simultaneously, have significantly influenced customer satisfaction by 41,74%.